2012
DOI: 10.4103/0974-2727.105590
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Tuberculosis (Pott's disease) Mimicking Paravertebral Malignant Tumor in a Child Presenting with Spinal Cord Compression

Abstract: Paravertebral tumors may interfere with the radiological and clinical features of spinal tuberculosis. We report a case of a 3-year-old boy with spinal tuberculosis who was initially misdiagnosed as having a paraspinal tumor. The diagnosis of tuberculosis was made on the basis of intraoperative findings and confirmed by histopathology. This case highlights the importance of awareness of the different radiographic features of spinal tuberculosis, which can mimic a spinal malignancy. In order to avoid delayed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…[ 1 20 ] The management of paraspinal lesions is aimed to confirm the diagnosis, either fine needle aspiration cytology or preferably by complete surgical resection. [ 5 21 22 23 ] To maintain the stability of the spine, we performed the partial unilateral laminotomy. In the present case, we could perform subtotal resection, and once we could confirm the diagnosis of tuberculosis, the patient received antitubercular treatment as per standard protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 20 ] The management of paraspinal lesions is aimed to confirm the diagnosis, either fine needle aspiration cytology or preferably by complete surgical resection. [ 5 21 22 23 ] To maintain the stability of the spine, we performed the partial unilateral laminotomy. In the present case, we could perform subtotal resection, and once we could confirm the diagnosis of tuberculosis, the patient received antitubercular treatment as per standard protocol.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Rarely, this paraspinal involvement can mimic malignant lesion and can be diagnostic challenge even in endemic countries. [ 1 3 4 5 6 7 8 ] In the present article, we report a case of an elderly man who presented with a large paraspinal tubercular lesion which was masquerading malignant lesion and review the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Ce n'est que devant l'absence de réponse au traitement anti bacillaire qu'une biopsie a été faite et le diagnostic corrigé. Emir et al ont, quant à eux, rapporté le cas d'un mal de Pott traité comme tumeur maligne para vertébral ; encore une fois c'est l'exploration chirurgicale et la biopsie qui a permis de redresser le diagnostic [ 7 ]. La biopsie est donc le seul garant d'un diagnostic de certitude par la mise en évidence d'un granulome épithélioïde giganto- cellulaire avec présence d'une nécrose caséeuse.…”
Section: Discussionunclassified
“…In a recent review from India [13] it was reported that its prevalence varied from 18 to 54%. Spinal TB was a rare disease found in children, which needed a higher index of suspicion for diagnosis, but caused important systemic symptoms [14], and might lead to a difficult differencial diagnosis [15]. Haemophagocitic Syndrome, another important immunological complication of TB, was rarely seen but it could lead to death in children [16].…”
Section: Clinical Findingsmentioning
confidence: 99%